2009
DOI: 10.1007/s00408-009-9150-x
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Injection Causing Acute Pneumonitis: A Case Series

Abstract: Local and systemic complications following injected silicone have been described, especially after cosmetic procedures by unlicensed practitioners. We report a retrospective case series of acute pneumonitis following silicone injection to the buttock. Medical records, pulmonary function tests, blood arterial gases, chest radiographs, and high-resolution computed tomography scans were reviewed. Five patients with acute pneumonitis after injected silicone were identified. All cases were men with a mean age was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
17
0
4
Order By: Relevance
“…8 Moreover, other reports also show a favorable response with the use of steroids in the treatment of these patients. 3,9 However, there is no consensus regarding the use of steroids yet.…”
Section: Discussionmentioning
confidence: 84%
“…8 Moreover, other reports also show a favorable response with the use of steroids in the treatment of these patients. 3,9 However, there is no consensus regarding the use of steroids yet.…”
Section: Discussionmentioning
confidence: 84%
“…In our patient, an acute pneumonitis was marked by a sudden shortness of breath, tachycardia, tachypnoea, fever, chest pain, and haemoptysis that appeared within 24 h after the silicone injection [1,2].…”
Section: Introductionmentioning
confidence: 60%
“…The respiratory consequences have been described as severe pulmonary toxicity, acute pneumonitis [1, 68], acute respiratory distress syndrome, and pulmonary embolism [9]. Pulmonary manifestations of subcutaneous silicone injections are proposed to result from inadvertent injection of silicone directly into a vein, increased tissue pressures at injection sites, and from local massage or trauma at the site.…”
Section: Discussionmentioning
confidence: 99%
“…Zamora et al [8] reported five cases of silicone-associated pneumonitis that all recovered with steroid treatment but admit that steroid responsiveness cannot be proven as there were no untreated patients with whom outcomes could be compared. Steroid therapy is often initiated in the setting of unexplained acute respiratory failure.…”
Section: Discussionmentioning
confidence: 99%